Implementation of the Literacy Journal Program in Strengthening Students’ Reading Interest - Teguh Wibowo; Mahariah Mahariah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyse the implementation of the Literacy Journal programme in strengthening students’ reading interest at SMP Islam Plus Al-Ikhlas Taqwa Medan. This research employed a qualitative method with a case study approach. The data sources consisted of the principal, vice principal, and students. Data were collected through observation, interviews, and documentation, while data validity was ensured through triangulation techniques. The findings reveal that the Literacy Journal programme was designed as a routine literacy habituation activity requiring students to read books daily and record the results of their reading in a literacy journal. The programme is supported by weekly literacy activities known as Kamis Literasi, where students present and reflect on the books they have read. The study shows that the programme contributes positively to strengthening students’ reading interest, improving communication skills, expanding vocabulary mastery, and fostering critical thinking abilities. In addition, the integration of English writing within the literacy journal reflects efforts to develop global literacy competencies among students. However, several challenges were identified, including limited library facilities, students’ dishonesty in filling out journals, and insufficient parental involvement. Therefore, collaboration between schools and families is essential to support the sustainability and effectiveness of literacy programs in developing students’ reading culture and educational quality